Re-looking at Robert Frost’s “Stopping By Woods on a Snowy Evening” through an Islamic Prism - Alam, Md (Advances in Social Sciences Research Journal, 2019)
This paper presents a possible new religious meaning of Robert Frost’s well-known poem “Stopping by Woods on Snowy Evening”. This new meaning exploration is carried through an Islamic reading of the text. The study investigated how much correspondence the poem shares with Islam and what representation of Islamic themes and teachings is possible to exist in the text. To this end, a critical analysis was done to ferret out religious essence contained in the poem. The analysis was based on the post-structuralism literary theory which expostulates that a text has no fixed meaning; in a text, there can be multiple meanings. Based on this theory, the analysis shows that the poem exhibits a drawing of Islamic inspiration for search for Allah, articulates philosophy about Islamic ways of life, presents justification of the good and bad of life, Allah’s prohibitions and commandments, and Muslim roles and responsibilities. The poem is thus infinitely of more value as a piece of literary work and reluctant readers of Muslim tradition might consider reading the poem with new greater religious significance. This study, thus, adds a new value to the poem.